Гендерний аспект у сучасному українському ретродетективі - Чорний, І. В.; Chornyi, I. V. (Вісник науки та освіти. - 2024. - № 3(21). - С. 406-419, 2024)
У статті розглядаються особливості створення образів жінок-детективів у сучасних українських ретродетективах, зокрема в циклах Андрія Кокотюхи «Київська сищиця», Лори Підгірної «Інеса Путс. Панянка-детектив із Проскурова» та «уманському» циклі Дмитра Безверхнього. Показано різноманіття підходів цих авторів до проблеми, чи враховують вони історичні реалії, стан гендерного питання в Російській імперії межі XIX-XX ст., адже існувала низка обмежень/заборон на ті або інші професії для жінок. В деяких творах поряд з вигаданими персонажами діють реальні історичні особи і практично в усіх відтворено місцевий колорит локацій, на яких відбуваються описувані події.

The modern Ukrainian historical-crime novel (or retrodetective) as a genre appeared in domestic literature not long ago, in the late 20th - early 21st centuries, but it has already won the favor of the readership and attracted the attention of literary researchers. Among the numerous problems associated with the functioning of this type of criminal genre, one of the main places is the question of the role and functions of the main character. And if the discussions surrounding the assessment of the status of the male hero have become less acute, then the problem of showing a female detective as the main protagonist has practically not been considered yet. Besides that, new retro-detective works in which the main character is a woman who investigates criminal crimes have appeared. Accordingly, the problem arises as to how believable is the attempt to build the plot of a historical crime novel on such a basis. The article examines the peculiarities of the creation of female detective’s images in modern Ukrainian retro-detectives, in particular in the cycles of Andrii Kokotiuha “Kyivska syshchytsia”, “Inesa Puts. The young lady-detective from Proskurov” by Lora Pidhirna, and the “Uman” cycle by Dmytro Bezverhnyi. The diversity of these authors' approaches to the problem is shown, whether they are considering historical realities, the state of gender issues in the Russian Empire at the turn of the XIX-XX centuries, because there were a number of restrictions/bans on certain professions for women. Only after the reforms of Alexander II some changes have begun. For example, in the sphere of Law, women were able to become private lawyers and notaries only in some cases. However, even there, there were only a few cases when a woman could hold on to these positions for a long time. At the same time, there was no discussion about allowing women to be engaged in official investigative and detective work. The authors of the considered works motivate their heroines' pursuit of detective work in different ways. This is either a way to get rid of boredom, everyday routine, or a desire to shock society, or hope to earn a piece of bread with their detective skills. In some works, along with fictional characters, the real historical figures act, and almost all of them reproduce the coleur locale of the locations where the described events take place.

В статье рассматриваются особенности создания образов женщин-детективов в современных украинских ретродетективах, в частности, в циклах Андрея Кокотюхи «Киевская сыщица», Лоры Подгорной «Инесса Путс. Барышня-детектив из «Проскурова» и «уманском» цикле Дмитрия Безверхнего. Показано разнообразие подходов этих авторов к проблеме, учитывают ли они исторические реалии, состояние гендерного вопроса в Российской империи на рубеже XIX-XX вв., ведь существовал ряд ограничений/запретов на те или иные профессии для женщин. В некоторых произведениях наряду с вымышленными персонажами действуют реальные исторические личности и практически у всех воспроизведен местный колорит локаций, на которых происходят описываемые события.
Gender aspect in modern Ukrainian retrodetective
Keywords: гендер; гендерний аспект; ретродетектив; історико-кримінальний жанр; образ; місцевий колорит; gender; gender aspect; retrodetective; historical mystery; image; coleur locale; гендерный аспект; историко-криминальный жанр; местный колорит